Influence Of Social Media Marketing Activity Instagram Towards Purchase Intention With Brand Equity And Electronic Word Of Mouth As Intervening Variables In Pass The Trend Bandung - Fariza Nurfaida Putri; Tarandhika Tantra (Jurnal Manajemen Bisnis Eka Prasetya, 2023)
The advancement of internet technology and the existence of social media is the right opportunity to open an online business amid the development of the internet in all aspects of society. One of the applications of this technology is the use of marketing strategies that can be carried out through social media. This study aims to determine whether social media marketing activities carried out by Pass The Trend have a positive influence on brand equity, the spread of e-WOM on social media, and customer purchase intention. The SEM-PLS measurement model and quantitative approach are used in this research methodology. Respondent data was collected through distributing questionnaires to 400 participants of Instagram social media users who had accessed Pass The Trend's Instagram account. The research shows that social media marketing activity has a positive impact on purchase intention. In addition, brand equity is also considered to have a positive effect on e-WOM and e-WOM still positively affects purchase intention. The results of this study are intended as an evaluation for Pass The Trend, providing insight into how to improve and implement social media marketing activities on Instagram effectively. This is expected to increase Pass The Trend's brand equity and e-WOM.